EVALUASI KINERJA GURU BIOLOGI DENGAN MODEL KERANGKA PENGAJARAN DANIELSON - Erfy Melany Lalupanda; Vidriana Oktoviana Bano (Universitas Negeri Malang, 2021)
Abstract: The purpose of this study was to evaluate the performance of Biology teachers in East Sumba Regency. This research is an evaluation research that uses a quantitative approach. The total population of the study was 44 biology teachers, with a sample of 20 teachers. The data collection technique used a questionnaire based on the teaching framework rubric by Charlotte Danielson. The data analysis technique used quantitative descriptive. The results of research in the domain of learning preparation, 45% of teachers are in the Basic category or good enough. In the domain of classroom environmental management, 70% of teachers are in the Proficient or good category. In the domain of the implementation of learning, 50% of the teachers were categorized as Basic or quite good. In the domain of professional responsibility, 55% of teachers are in the Basic category. These results indicate that the performance of Biology teachers in East Sumba Regency needs to be improved, especially in the domains of learning preparation, learning implementation and professionalism. Keywords: Performance Evaluation; Biology Teacher; Charlotte Danielson. Abstrak: Tujuan penelitian ini adalah untuk mengevaluasi kinerja guru Biologi di Kabupaten Sumba Timur. Penelitian ini merupakan penelitian evaluasi yang menggunakan pendekatan kuantitatif. Jumlah populasi penelitian adalah 44 orang guru Biologi, dengan sampel yang diteliti 20 orang guru. Teknik pengambilan data menggunakan kuesioner berdasarkan Rubrik kerangka pengajaran oleh Charlotte Danielson. Teknik analisis data menggunakan deskriptif kuantitatif. Hasil penelitian pada domain persiapan, 45% guru berada pada kategori Basic atau cukup baik. Pada domain pengelolaan lingkungan kelas, 70% guru berada pada kategori Proficient atau baik. Pada domain pengajaran, 50% guru berkategori Basic atau cukup baik. Pada Domain Tanggungjawab profesional 55% guru berkategori Basic. Hasil ini menunjukkan bahwa kinerja guru Biologi Kabupaten Sumba Timur perlu untuk ditingkatkan khususnya pada domain persiapan pembelajaran, pengajaran dan profesionalitas. Kata kunci: Evaluasi Kinerja; Guru Biologi; Model Charlotte Danielson.